PENURUNAN KANDUNGAN ZAT PENCEMAR ORGANIK PADA LIMBAH RUMAH POTONG AYAM DENGAN BIOFILTER AEROB MENGGUNAKAN MEDIA KULIT KERANG - Novirina Hendrasarie; Evi Wahyu Ardhi (EnviroUS, 2022)
Liquid waste in the Chicken Slaughterhouse (RPA) has a high organic pollutant, as well as contains various microorganisms that can be pathogenic. In this study, the processing unit used was an aerobic biofilter with a batch system, using Neptunea Cumingii skin and Anadara Granosa skin adhesive media, at contact times of 12, 24, 36, 48 hours. This study aims to determine the type of media and the best contact time and microorganisms that play a role in reducing the content of BOD, COD, TSS, and Ammonia. The results showed that the most optimal result was using Anadara Granosa skin media with a contact time of 48 hours, it could reduce the concentration of BOD 96.24%, COD 90.27%, TSS 98.18% and Ammonia 98.86%. Microorganisms that play a role in degrading organic content in chicken slaughterhouse waste on Neptunea Cumingii skin media are Comamonas testosterone, Anadara Granosa skin media are Aeromonas sobria and Salmonella spp.